2010
DOI: 10.1097/gim.0b013e3181f13a4a
|View full text |Cite
|
Sign up to set email alerts
|

Agalsidase beta treatment is associated with improved quality of life in patients with Fabry disease: Findings from the Fabry Registry

Abstract: Purpose:To evaluate the effect of agalsidase beta on longitudinal healthrelated quality of life in patients with Fabry disease. Methods: The SF-36 Health Survey was used to measure health-related quality of life in Fabry Registry patients. Seventy-one men and 59 women who were treated with agalsidase beta (median dose: 1.0 mg/kg/2 weeks) and who had baseline and at least 2 yearly posttreatment health-related quality of life measurements were included in these analyses. A repeated measures model was used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 34 publications
(59 reference statements)
0
64
0
Order By: Relevance
“…The results of the present (Crosbie et al 2009;Gold et al 2002;Masek et al 1999;Packman et al 2006;Watt et al 2010;Weinreb et al 2007;Wilcox et al 2008). Prevalence estimates of depression in FD range from 15 to 62% (Bolsover et al 2014;Grewal 1993;Wang et al 2007), with the largest study (n ¼ 296) reporting 46% (Cole et al 2007).…”
Section: Discussionmentioning
confidence: 55%
“…The results of the present (Crosbie et al 2009;Gold et al 2002;Masek et al 1999;Packman et al 2006;Watt et al 2010;Weinreb et al 2007;Wilcox et al 2008). Prevalence estimates of depression in FD range from 15 to 62% (Bolsover et al 2014;Grewal 1993;Wang et al 2007), with the largest study (n ¼ 296) reporting 46% (Cole et al 2007).…”
Section: Discussionmentioning
confidence: 55%
“…Fabry male patients were tested when already on ERT and their results were compared with female heterozygotes who had no access to the therapy. Although it is well known that ERT affects QoL for both genders [16,18], in our sample males on ERT tended to have lower QoL in terms of EQ-VAS, EQ-index and EQ dimensions, than females without ERT.…”
Section: Discussionmentioning
confidence: 47%
“…Global reduction of QoL in patients with Fabry disease has been confirmed in studies using SF-36 questionnaire [2,3,[14][15][16]. Gold et al found that patients with Fabry disease have a score profile most similar to patients with AIDS and that in comparison with patients with Gaucher disease, Fabry patients score substantially lower across all QoL domains [2].…”
Section: Discussionmentioning
confidence: 90%
“…Enzyme activity in leukocytes is always very low in affected males but may be normal or borderline normal in symptomatic affected females whose diagnosis needs to be confirmed by the genetic analysis. Current treatments consist of enzyme replacement therapy (ERT) and palliative treatments [6][7][8][9][10][11][12][13]. Two agalsidase preparations, agalsidase alfa and agalsidase beta, are available for ERT.…”
mentioning
confidence: 99%